Review: Metabolit Sekunder pada Kelapa Sawit - Mira Ariyanti; Farida Farida; Uum Umiyati (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Oil palm is known as a plantation crop that produces vegetable oil which is widely used in human life. Palm oil is produced from fresh fruit bunches (FFB) which originate from female flowers. Another part of the oil palm plant that has not been widely utilized is the oil palm leaves. When these leaves have been pruned, they will become abundant garden waste. Apart from that, there are empty palm oil bunches (tankos) which are classified as factory waste. Further research is needed regarding the compound content, especially the secondary metabolite content of midrib and tankos so that their utilization is optimal. The aim of this review is to determine the content of secondary metabolite compounds in oil palm plants and the potential for wider use. The method used is collecting library data, reading, analyzing and writing it down. The data and references used are scientific articles in national and international journals, textbooks, literature reviews and other sources. Based on the review, information was obtained that oil palm leaves contain several secondary metabolite compounds, especially saponins and phenols, while tankos contains phenol compounds. The amount of secondary metabolite compound content is not yet known for certain and this could be an opportunity to conduct research to determine the content of secondary metabolite compounds, especially for oil palm plants.